2014
DOI: 10.1016/j.visres.2014.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Local spectral anisotropy is a valid cue for figure–ground organization in natural scenes

Abstract: An important step in the process of understanding visual scenes is its organization in different perceptual objects which requires figure-ground segregation. The determination which side of an occlusion boundary is figure (closer to the observer) and which is ground (further away from the observer) is made through a combination of global cues, like convexity, and local cues, like T-junctions. We here focus on a novel set of local cues in the intensity patterns along occlusion boundaries which we show to differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 36 publications
(58 reference statements)
5
16
0
Order By: Relevance
“…While the contours included in natural and filled patches are the same, the other content features, including texture, color, and shading, could improve neuronal FG discrimination. Ramenahalli et al [14] reported that local spectral anisotropy between the figure and ground sides along a contour was capable of yielding a rate of correct FG assignment of almost 70%, using SVM. This result suggests that texture and shading include a fair amount of information that can be used for FG discrimination, although it is currently unclear how much information is used by V4 neurons.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…While the contours included in natural and filled patches are the same, the other content features, including texture, color, and shading, could improve neuronal FG discrimination. Ramenahalli et al [14] reported that local spectral anisotropy between the figure and ground sides along a contour was capable of yielding a rate of correct FG assignment of almost 70%, using SVM. This result suggests that texture and shading include a fair amount of information that can be used for FG discrimination, although it is currently unclear how much information is used by V4 neurons.…”
Section: Plos Onementioning
confidence: 99%
“…In all these pioneering studies, the responses of single cells to well-controlled stimuli, such as textured squares, luminance-defined rectangles, and parameterized curvatures, were examined with the careful selection of cells based on their stimulus selectivity (e.g., orientation, color, and shape) and the spatial relations of their classical receptive fields (CRFs) with respect to the stimulus. [10] Recent studies have investigated FG organization in natural scenes, reporting crucial factors for FG based on local image features including contour shapes [11][12][13] and spectral anisotropy [14]. V2 neurons were shown to be selective to border ownership in natural images [15].…”
Section: Introductionmentioning
confidence: 99%
“…The EE on the outer side of the inner edge of a torus (or donut), for example, is easily perceived as the closer figure, even though it is highly concave and fully surrounds the visible region of the surface visible through the central hole. In complex natural scenes, figure-ground organization is processed from a combination of information about global features (e.g., region convexity) and local features (e.g., T-junctions) (Ramenahalli, Mihalas, & Niebur, 2011, 2014. Because EEs can be extracted from local spatial filters around the edge, they are more efficient for figure-ground computations than global properties.…”
mentioning
confidence: 99%
“…In fact, Geisler and Perry ( 2009 ) observed that edges with an inconsistent polarity are less likely to belong to the same contour. Recently, it has been reported that even low-level cues, such as the sharpness of an edge or local anisotropies in spectral power can be informative about figure-ground organization (Ramenahalli et al, 2014 ; Vilankar et al, 2014 ).…”
Section: Intermediate Computationsmentioning
confidence: 99%